Reduction of Exfoliated MoS2 Nanosheets Yields the Semi-Conducting 2H-polymorph Rather Than the Metallic 1T-polymorph - Mc Donald, Aidan (My University, 2024)
Delaminated two‐dimensional (2D) transition metal dichalchogenides (TMDs) have attracted significant attention due to their potential application in electronics, catalysis, and biomedical devices. Chemical derivation of TMDs often relies on the generation of a metallic polymorph (1T) which is unsuitable for such applications. We explored the reactivity of the semi‐conducting polymorph (2H) of pre‐exfoliated MoS2 nanosheets (as a model TMD). Pristine liquid exfoliated 2H‐MoS2 was reacted with NaBH4. A novel reduced two‐dimensional TMD, r‐2H‐MoS2, was identified as evidenced by electronic absorption, XPS, photoluminescence, DRIFT, and Raman spectroscopies, and cyclic voltammetry. The material demonstrated a full preservation of the semi‐conducting phase rather than conversion to the metallic 1T‐nanomaterial that is commonly observed in the chemical derivation/exfoliation of TMDs.
Keywords: transition metal dichalchogenides (TMDs); Raman spectroscopies; MoS2